A theory of economic policy lock-in and lock-out via hysteresis: Rethinking economists' approach to economic policy - Thomas I. Palley (Kiel Institute for the World Economy (IfW), 2016)
This paper explores lock-in and lock-out via economic policy. It argues policy decisions may near-irrevocably change the economy's structure, thereby changing its performance. That causes changed economic outcomes concerning distribution of wealth, income and power, which in turn induces locked-in changes in political outcomes. That is a different way of thinking about policy compared to conventional macroeconomic stabilization theory. The latter treats policy as a dial which is dialed up or down, depending on the economy's state. Lock-in policy is illustrated by the euro, globalization, and the neoliberal policy experiment.
Keywords: D7; E6; F5; H3; L5; 330; economic policy; lock-in; hysteresis; globalization; euro; neoliberalism